The tournaments at Le Hem and Chauvency : Sarrasin : The romance of Le Hem : Jacques Bretel : The tournament at Chauvency - Bryant, Nigel, 1953-; Sarrasin; Bretel, Jacques (The Boydell Press, 2020)
"The Romance of Le Hem and The Tournament at Chauvency are eyewitness accounts of the famous tournaments held in 1278 at Le Hem on the banks of the Somme in north-eastern France, and in 1285 at Chauvency in Lorraine. Written within weeks of the events they describe, they record in vivid detail not only the jousts and the mêlées but also the entertainments and dramatic interludes which preceded, followed and embellished these festivals of martial sport. As Sarrasin makes clear, theatre as well as jousting, and jousting in the context of enacted stories, were central to what took place at Le Hem, involving elaborate role-play by participants as figures from Arthurian romance. And few medieval accounts of events have such thrilling immediacy as Jacques Bretel's record of Chauvency. He sat in a prime place, on the fourth step of the stand, and the reader sees and hears the action as if sitting at his shoulder - and eavesdrops on conversations, too. He gives remarkable insights into the surprising role played by song, and into how the whole event was perceived and understood. These intriguing works are invaluable source material for scholars not only of medieval chivalry and tournaments but also of festivities and performance."--